Challenges in the Management of Giant Carcinoma Ex-Pleiomorphic Adenoma of the Parotid Gland in a Single Tertiary Center - Miruna Bratiloveanu; Mihai Dumitru; Andreea Nicoleta Marinescu; Crenguta Serboiu; Oana Maria Patrascu; Adrian Costache; Daniela Vrinceanu (Medicina)
Background and Objectives: Carcinoma ex-pleiomorphic adenoma (CXPA) is a carcinoma derived from a primary or recurrent pleiomorphic adenoma. Microscopically, non-invasive CXPA (intracapsular and carcinoma in situ), minimally invasive CXPA (extracapsular invasion less than 1.5 mm), and invasive CXPA (extracapsular invasion more than 1.5 mm) are described. Materials and Methods: We performed a retrospective clinical study over the period of 2009–2023 in patients admitted to the ENT Department of the Bucharest University Emergency Hospital. Results: In the studied group, there was a net male predominance of 2.5:1. The tumor evolution until presentation was 6.64 years on average, with values between 2 and 20 years. The reasons for presenting to our department included a sudden increase in size in eleven cases (78.57%), pain in nine cases (64.29%), peripheral facial paralysis in eight cases (57.14%), skin invasion/ulceration in five cases (35.71%), and massive tumor hemorrhage in one case (7.14%). There were histopathological results on paraffin of myoepithelial CXPA in four cases (28.57%), of high-grade CXPA (salivary duct, secretory) in eight cases (57.14%), and of squamous CXPA in two cases (14.29%). The patients with unfavorable evolution showed the following characteristics: a tumor diameter over 11 cm (four cases), integument invasion (four cases), perivascular invasion at HP exam (six cases), perineural invasion at HP exam (six cases), and invasion of the ganglion (three N3b cases and two N1 cases). Conclusions: CXPA is a neoplasia that, when associated with large tumor volumes or peripheral facial paralysis in particular, is a challenge for both the doctor and patient.